Fabrication and characterization of graphene and carbon nanotube reinforced bioceramic nanocomposites - Hu, Huanlong (Nanyang Technological University, 2020)
Bioceramics play an important role in the replacement and regeneration of human tissues, but their intrinsic brittleness and low wear resistance make the monolithic bioceramics still problematic for load-bearing applications. The two dimensional (2D) graphene and one dimensional (1D) carbon nanotube (CNT), as the secondary strong and tough biocompatible nanofillers, are popular nanocarbons to reinforce bioceramics. However, their utilization as high-performance reinforcements in bioceramics is not fully exploited because of several significant challenges, including agglomerations of nanocarbons and the weak interfaces between nanocarbons and matrixes. This research aimed to utilize the advantages of graphene and CNT as nanosized reinforcements to enhance the mechanical and tribological properties of bioceramics. This research specifically investigated the following: (1) the effects of reduced graphene oxide (rGO) content and mixing method on the structural and mechanical properties of rGO-reinforced hydroxyapatite (HA) composites; (2) the effect of nanocarbon morphologies on the structural and mechanical properties of nanocarbon-reinforced HA composites; and (3) the evaluation of the tribological behaviors of nanocarbon-reinforced HA composites at micro- and nano- scales. In terms of nanocarbon content, monolithic HA and HA reinforced with various contents of rGO (0, 1, 2, 5, and 10 wt%) were prepared and characterized. The hardness, Young’s modulus and fracture toughness of the composites were increased with up to 2 wt% rGO and reduced with 5 and 10 wt% rGO as reinforcements. With increasing rGO concentration, the densification rate decreased, and the number of rGO agglomerations and porosities increased. The improvement in mechanical properties was mainly attributed to the microstructure refinement of the composites, and the crack bridging and branching mechanisms of rGO. Regarding mixing methods, all the ultrasonication mixed and ball milled 1 wt% rGO reinforced HA composites were almost fully densified. The hardness and fracture toughness of SPSed pellets were improved in all the rGO-HA composites, and the highest values were obtained in the composite mixed with ultrasonication in ethanol solvent. Although the high-speed wet ball milling method facilitated the satisfactory dispersion of nanocarbons into HA bioceramics, a large number of defects were introduced simultaneously. In contrast, ultrasonication mixing method was superior with similar dispersion efficiency but fewer defects generated on rGO. When one type of nanocarbons was used, the size and shape of the nanocarbons significantly influenced the structural and mechanical behaviors of the reinforced composites. The highest hardness and fracture toughness were obtained from SPSed rGO-HA and the CNT-HA composites, with 30.6% and 43.1% improvements over the pure HA samples, respectively. In rGO-HA composites, the rGO plates with large lateral dimensions could wrap HA grains for finer and layered microstructures for higher hardness. In CNT-HA composites, the interactions between CNTs and HA matrixes were enhanced by the formation of the unique mechanical locking structures in CNTs. When rGO and CNT hybrid were used as reinforcements, the optimum dispersion of rGOs and CNTs, and the strong interface bonding between the nanocarbons and HA matrixes were established in the composites. Furthermore, the small-sized CNTs were found inserted into rGO plates in the mixed powder and sintered pellets. As a result, the HA composite reinforced with rGO and CNT hybrids showed a significant improvement in mechanical properties. They exhibited higher hardness and fracture toughness than the ones reinforced with one type of nanocarbon. In the micro-scale ball-on-disk tribological tests, the wear and friction behaviors were strongly dependent on nanocarbon content and morphology. By increasing the total nanocarbon contents from 1 wt.% to 2 wt.%, the wear resistances of both rGO and rGO + CNT hybrids reinforced composites were substantially increased. Under 2 wt% total nanocarbon content and with the morphology of rGO/CNT hybrid, the wear resistant was improved up to ~17 times that of monolithic HA. In the nano-scale tribological tests, the wear and fatigue performances depended on nanocarbon morphology, nanocarbon content, normal force, and wear velocity. The maximum wear track deformation and wear volume loss demonstrated nearly perfect quadratic and linear relations, respectively. The 1 wt% rGO based composites exhibited ~3.35 times lower wear rate than that of pure HA sample under 1 µm/s scratching speed and 5 mN normal force conditions. The reinforcing mechanism was due to the lubrication and pinning effects of rGO, which resulted in high resistance to penetration, elastic recovery capability, low-cycle fatigue resistance, and microcrack propagation inhibition properties. Therefore, by varying nanocarbon content and mixing method, and nanocarbon morphology, the HA bioceramics were strengthened and toughened. In addition, the tribological results at both micro- and nano- scales suggested that rGO and CNT reinforced HA bioceramic composites had higher long-term capabilities to sustain the complex environments and load scales when used as artificial substrates in human beings. The mechanical and tribological results suggested the clinical applications of HA were expected to be extended with rGO and CNT as reinforcements.